Psichiatria o antipsichiatria? Indagine sulle correnti della psichiatria istituzionale in Europa - Ellenberger , Henri F. (Il sogno della farfalla, 2024)
In 1970 the psychiatrist and historian of psychiatry Henri F. Ellenberger conducted a research in several European psychiatric institutions. The aim was to introduce the anti-psychiatry movement within the currents of institutional psychiatry contemporary to his time. He therefore visited and analysed facilities oriented according to different theoretical framework, from those of Maxwell Jones’s therapeutic community, to those of ‘institutional psychotherapy’, including the anti-psychiatry current. In this way, Ellenberger aimed to investigate the origins of the anti-psychiatry movement, its extension, and its deeper meaning, as well as to verify its penetration and concrete application within treatment institutions. Being critical towards the basic assumptions of this movement, the author went so far as to emphasize the iatrogenic risks inherent in anti-psychiatric thinking. We publish this intervention, unpublished in Italy, as a relevant contribution to the current debate.